TECHNOLOGIES OF MANAGING ATTITUDE TO A HEALTHY LIFESTYLE AS PREVENTION OF DEVIATIONS OF STUDENTS OF THE INSTITUTE OF PHYSICAL CULTURE - Popova, N.V.; Krutko, I.S.; Arslanbekova, E.M. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify the effectiveness of the use of technologies for managing attitudes towards a healthy lifestyle as a prevention of student deviation in the university under study. Methods and structure of the study. The empirical part of the study included three stages: Stage 1 - conducting a pre-project analysis using the questionnaire method (100 students were interviewed); 2nd stage - development and implementation of the project "Students-Healthy Lifestyle Center"; 3rd stage - determination of the effectiveness of the project implementation by the method of formalized interviews (20 people were interviewed). Results and conclusions. The results of the study showed the presence of an average level of students' awareness of the technologies for managing attitudes towards healthy lifestyles as the prevention of youth deviations and the need to improve them. The authors developed and implemented the project "Students-Healthy Lifestyle Center", aimed at developing healthy lifestyle skills through managing their health, time, resources, nutrition, the results of which revealed that this project is a technology of social design and contributes to the modernization and increase in positive impact on young people of preventive techniques, which will reduce the number of deviations among young people.